RBM47 promotes cell proliferation and immune evasion by upregulating PDIA6: a novel mechanism of pancreatic cancer progression - Yihui Ma; Enjie Liu; Huijie Fan; Chenfei Li; Pei Huang; Meiying Cui; Zhengyang Wang; Jing Zhou; Kuisheng Chen (Journal of Translational Medicine)
Abstract Background Pancreatic cancer (PC) is a lethal malignancy characterized by poor prognosis and high mortality. We found the highly expressed RNA-binding motif protein 47 (RBM47) in PC progression. The RBM47 expression was negatively correlated with natural killer (NK) cell infiltrate in PC. Moreover, RBM47 was predicted to bind to the 3′-UTR region of Protein Disulfide Isomerase Family A Member 6 (PDIA6), an oncogene of the development of PC. Therefore, we supposed that RBM47 might affect PC progression by regulating PDIA6. Methods Bioinformatics analysis was performed to screen the candidate gene affecting PC progression using public databases. Loss- and gain-of-function effects of RBM47 on cell proliferation, tumor growth, and immune evasion were determined by CCK-8, EdU incorporation, colony formation assays, the xenogeneic tumor model, and co-culture system of PC and NK-92 cells. RBM47-RNA immunoprecipitation (RIP) followed by PCR and dual luciferase reporter assay were used to detect whether RBM47 could interact with the PDIA6 mRNA and how RBM47 would regulate the transcriptional activity of PDIA6, respectively. Simultaneous overexpression of PDIA6 in RBM47 knockdown PC cells was conducted to clarify whether PDIA6 would mediated effects of RBM47. Given the important role of cellular metabolism in cells proliferation and immune evasion, PC cells with RBM47 knockdown were subjected to metabolomics analysis to further investigate how RBM47 regulate PC progression. Results RBM47 overexpression drove PC progression by promoting cell proliferation and xenografted tumor growth. Consistently, our results showed that RBM47 overexpression weakened sensitivity of PC cells to cytotoxic NK cells. However, RBM47 knockdown exhibited the opposite effects on proliferation and immune evasion of PC cells. RBM47 was able to bind to the 3′-UTR region of PDIA6, maintained PDIA6 mRNA stability, and increased the PDIA6 expression in PC cells. Rescue experiments supported that PDIA6 overexpression reversed the suppressing effects of RBM47 knockdown on cell proliferation and immune evasion. RBM47 knockdown significantly changed metabolites of PC cells. Conclusions In summary, our findings demonstrate that RBM47 contributes to PC progression, which might be mediated by the upregulated PDIA6 expression and the altered cellular metabolites in PC cells, offering a potential therapeutic target for PC treatment. Graphical Abstract